Răspunsuri

2014-10-24T20:06:44+03:00
A) d divide (2n-1) ⇒ d divide 2(2n-1) =4n- 2    (1)
d divide (4n+5)  (2) ⇒ d divide [ (2) -(1)] = 7    ptr/ 2n-1 =7 ⇒n=4  4n+5=21 ⇒7 divide 21
b) d divide (3n+2) ⇒ d divide 3(3n+2) = 9n+6  (1)
   d divide (9n+17)  (2)  ⇒  d divide [(2) -(1)] =11 
divizorii lui 11 sunt 1 si11      I. 3n+2 =1 ⇒n∉N
II. 3n+2 =11 ⇒n=3    9n+17 = 44 ⇒11 divide 44
c) d divide (2n+1)⇒ d divide 3(2n+1) = 6n+3  (1)
   d divide ((3n+5) ⇒d divide 2(3n+5) =6n+10  (2) ⇒d divide [(2) -(1)]=7; divizorii lui 7 sunt 1 si 7 ⇒  I. 2n+1 =1 n=0    3n+5 =5  1 divide 5
II. 2n+1 =7  2n=6 n=3  3n+5=14  7 divide 14
d)  n²+n+17 = n²+6n+9 - 5n+8 = (n+3)²+(8-5n)
(n+3) divide (n+3)² ⇒  trebuie ca (n+3) sa divida (8-5n)
daca: d divide  (n+3) ⇒ d divide 5(n+3)=5n+15  (1)
          d divide (8-5n)    (2) ⇒d divide [(1)+(2)]=23
n+3 =23 ⇒n=20  n² +n +17 = 437  23 divide 437    (437=23×19)

6 4 6